Pengaruh Brand Image terhadap Keputusan Pembelian Produk Scarlett Whitening - Muliatul Khasanah; Nur Syamsiyah (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
The development of the times in terms of technology and economics is now increasingly rapid. Likewise the beauty industry. This makes brands increasingly aggressive in improving and introducing their brand image. Scarlett whitening is one of the most popular beauty products currently. This research aims to determine and analyze the influence of brand image on purchasing decisions among students from the class of 2020 and 2021 majoring in sharia economics at IAIN Metro. This research uses quantitative methods and the technique used in sampling is a probability sampling technique using proportional random sampling. The sample in this research consisted of 66 students. The data analysis tools in this research are validity test, reliability test, classical assumption test, simple linear regression test, t test and coefficient of determination test. The results of the research show that Ha is accepted and Ho is rejected, so it can be said that brand image has a positive influence on purchasing decisions for Scarlett Whitening products among students from the class of 2020 and 2021, majoring in sharia economics at IAIN Metro.